Investigation of in-cabin volatile organic compounds (VOCs) in taxis; influence of vehicle's age, model, fuel, and refueling. (June 2018) - Bakhtiari, Reza; Hadei, Mostafa; Hopke, Philip K.; Shahsavani, Abbas; Rastkari, Noushin; Kermani, Majid; Yarahmadi, Maryam; Ghaderpoori, Afshin
Abstract: The air pollutant species and concentrations in taxis' cabins can present significant health impacts on health. This study measured the concentrations of benzene, toluene, ethylbenzene, xylene (BTEX), formaldehyde, and acetaldehyde in the cabins of four different taxi models. The effects of taxi's age, fuel type, and refueling were investigated. Four taxi models in 3 age groups were fueled with 3 different fuels (gas, compressed natural gas (CNG), and liquefied petroleum gas (LPG)), and the concentrations of 6 air pollutants were measured in the taxi cabins before and after refueling. BTEX, formaldehyde, and acetaldehyde sampling were actively sampled using NIOSH methods 1501, 2541, and 2538, respectively. The average BTEX concentrations for all taxi models were below guideline values. The average concentrations (±SD) of formaldehyde in Model 1 to Model 4 taxis were 889 (±356), 806 (±323), 1144 (±240), and 934 (±167) ppbv, respectively. Acetaldehyde average concentrations (±SD) in Model 1 to Model 4 taxis were 410 (±223), 441 (±241), 443 (±210), and 482 (±91) ppbv, respectively. Refueling increased the in-vehicle concentrations of pollutants primarily the CNG and LPG fuels. BTEX concentrations in all taxi models were significantly higher for gasoline. Taxi age inversely affected formaldehyde and acetaldehyde. In conclusion, it seems that refueling process and substitution of gasoline with CNG and LPG can be considered as solutions to improve in-vehicle air concentrations for taxis. Graphical abstract: Image 1 Highlights: Concentrations of 6 air pollutants were measured in taxis' cabin. Effects of taxis' age and model, fuel, and refueling were investigated. Refueling increased concentrations of pollutants for CNG and LPG fuels. BTEX concentrations in all vehicle models were significantly higher for gasoline. Vehicle age inversely affected formaldehyde and acetaldehyde. Abstract : The concentrations of BTEX, formaldehyde and acetaldehyde were measured in 4 taxi models with different ages and fuels.